The place of humanities in our universities - Miri, Mrinal,Ed (Routledge, 2018)
This volume examines the critical role of the humanities in universities in India and attempts to redefine its place, meaning and function in education. Bringing together distinguished scholars in the country, it debates the status and predicament of the humanities in the academic programmes within universities. The issues raised here touch upon the entire gamut of problems that a university faces in finding an adequate, rightful and wholesome place for the humanities in its academic curriculum. It discusses the difficulties in the specific identity of disciplines classed under the humanities, the powerful reach of the sciences and technological inroads in the teaching and practice of all disciplines, the relative academic balancing of disciplines in different universities in India, the culture, value and the idea of the university, digitisation of the humanities and online access and their specific impact on research in the concerned disciplines. The volume also presents an instructive debate on the so-called appropriation of traditional social science concerns by other departments.